Integration of Antimicrobials and Delivery Systems: Synergistic Antibiofilm Activity with Biodegradable Nanoemulsions Incorporating Pseudopyronine Analogs - Jungmi Park; Neel Mahida; Gabrielle Ho; Elizabeth Pena; Jessa Marie V. Makabenta; Stanley Aneke; Mingdi Jiang; Leah M. Bouthillette; Stephanie E. Holz; Muhammad Aamir Hassan; Amanda L. Wolfe; Vincent M. Rotello (MDPI AG, 2023)
Multi-drug-resistant (MDR) bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), pose a significant challenge in healthcare settings. Small molecule antimicrobials (SMAs) such as α-pyrones have shown promise as alternative treatments for MDR infections. However, the hydrophobic nature of many SMAs limits their solubility and efficacy in complex biological environments. In this study, we encapsulated pseudopyronine analogs (PAs) in biodegradable polymer nanoemulsions (BNEs) for efficient eradication of biofilms. We evaluated a series of PAs with varied alkyl chain lengths and examined their antimicrobial activity against Gram-positive pathogens (S. aureus, MRSA, and B. subtilis). The selected PA with the most potent antibiofilm activity was incorporated into BNEs for enhanced solubility and penetration into the EPS matrix (PA-BNEs). The antimicrobial efficacy of PA-BNEs was assessed against biofilms of Gram-positive strains. The BNEs facilitated the solubilization and effective delivery of the PA deep into the biofilm matrix, addressing the limitations of hydrophobic SMAs. Our findings demonstrated that the PA2 exhibited synergistic antibiofilm activity when it was loaded into nanoemulsions. This study presents a promising platform for addressing MDR infections by combining pseudopyronine analogs with antimicrobial biodegradable nanoemulsions, overcoming challenges associated with treating biofilm infections.